Analisis Tata Letak Mesin ATM terhadap Kenyamanan dan Efektivitas Sirkulasi Antrian Pengunjung di ATM Center - Andrianto, Andrianto (Waca Cipta Ruang, 2022)
Due to the significance of ATM Centers in public areas, this facility must be able to meet all user comfort requirements. Based on preliminary information, there are issues with the configuration of the ATM machines at the Trans Studio Mall in Bandung, which are in the shape of an open letter L and impact user flow when queuing by allowing cross circulation that can disrupt the flow of the line and inconvenience customers when conducting banking activities. Visitors should be able to enjoy themselves while at Trans Studio Mall Bandung, the shopping center that offers this facility. Therefore, this study intends to comprehend and assess the needs of visitors so that banking activities at ATM Centers, particularly in malls, can function safely and comfortably. Based on this phenomena, this research was carried out using a case study methodology through interviews and direct observation at the ATM Center, which was then evaluated using descriptive qualitative methodologies based on theories linked to circulation, queuing, and public places. In order to promote comfort and effective visitor circulation when queuing at public facilities, the results of this study can be utilized as a reference in improving services, particularly in the sectors of design and banking. Keywords: ATM, circulation, publik space, queue